PENGARUH PROMOSI PENJUALAN, PEMASARAN MEDIA SOSIAL, DAN MOTIVASI BELANJA HEDONIS TERHADAP PERILAKU PEMBELIAN IMPULSIF : Studi Kasus Pengguna Gopay di Kota Bekasi - Nazmia Baladini (2021)
The purpose of this study is to prove that there is an effect of sales promotion on impulsive buying behavior, social media marketing on impulsive buying behavior and hedonic shopping motivation on impulsive buying behavior. This research is a quantitative study with primary sources of data. The object of this research is(are) Gopay users who are active in Bekasi City. The sample used was 100 respondents and dominated by students with accidental sampling technique as a sampling technique. The data analysis technique used is descriptive and essential data analysis techniques. Based on the results of data processing through t-statistics on Smart PLS, it can be shown that sales promotions have no significant effect on impulsive buying behavior, with a significance value of 0.512. Meanwhile, social media marketing and hedonic shopping motivation have a significant effect on impulsive buying behavior, with significance values of 3,553 and 3,768, respectively. From the research results, it is better if Gopay can improve social media marketing and take advantage of hedonic shopping motivation to increase transactions through impulsive buying behavior.